Effective Enhancement of Humidity Sensing Characteristics of Novel Thermally Treated MWCNTs/Polyvinylpyrrolidone Film Caused by Interfacial Effect. Issue 15 (11th May 2016) - Pan, Xinglong; Xue, Qingzhong; Zhang, Jianqiang; Guo, Qikai; Jin, Yakang; Lu, Wenbo; Li, Xiaofang; Ling, Cuicui
Abstract : Multi‐walled carbon nanotubes (MWCNTs)/hydrophilic poly(vinylpyrrolidone) (PVP) films are prepared by a simple spin‐coating method and the resistive humidity sensing properties of the films are studied in detail. It is demonstrated that the thermally treated MWCNTs/PVP film exhibits a reproducible and great response over a wide relative humidity range from 11% to 94%, fast response time (less than 15 s) and ultrafast recovery time (less than 1.8 s), which are superior to that of pristine PVP films. The effective enhancement of humidity sensing characteristics of MWCNTs/PVP films can be explained by the MWCNTs/PVP interfacial effect. The thermally treated MWCNTs/PVP films can be used as robust, cost‐effective, and easy‐to‐use resistive humidity sensors. And the design concept used in this work can be extended to other carbon composites to fabricate excellent sensing materials for sensors. Abstract : Multi‐walled carbon nanotubes (MWCNTs)/(poly(vinyl‐pyrrolidone) (PVP) films are prepared by spin‐coating method. The thermally treated MWCNTs/PVP film exhibits a reproducible and great response over a wide relative humidity range from 11% to 94%, fast response time and ultrafast recovery time due to the MWCNTs/PVP interfacial effect and stability of MWCNTs.